Analysis of the Motivation of Islamic Studies Students in Choosing Student Activity Units - Asril, Zainal; Langputeh, Sukree; AZ, Sudirman (Al-kayyis: Journal of Islamic Education, 2023)
College is not only a place to gain academic knowledge but also an environment that offers various opportunities for students' personal and social development. One form of extracurricular activity that is the focus of this research is the Student Activity Unit. This research aims to find out what the real motivation is for Islamic Studies students at universities who choose the Student Activity Unit. This research uses a qualitative method with a case study approach (case study design). The data source was taken from ten informants through in-depth interviews who were selected using purposive sampling techniques, all informants were active students of Islamic Studies at universities who chose Student Activity Units for the 2018, 2019 and 2020 entry years. All interview results were then analyzed thematically using the software Nvivo Qualitative Analysis 10. Overall the results of the analysis show that there are five motivations for Islamic Studies students in choosing Student Activity Units. The five motivations are: i) self-desire, ii) increasing knowledge, iii) seeking experience, iv) expanding relationships and v) hobby. The results of this research can be used as initial data for future researchers in studying this problem in different contexts and issues.